Using kindle fire HD - Wilson, Kevin (Apress, 2014)
Learn how to use your Kindle Fire with ease and no jargon. Clear, concise, short and to the point... Using Kindle Fire HD, is the essential guide to getting around Amazon's tablet/e-book reader. This book explores setting up your new Kindle and registering; navigating around the interface and what all the buttons, lists and icons are for; configuring your WiFi; keeping your kids safe when they use the device with parental controls; setting up, sending and receiving emails using Yahoo, Gmail or Hotmail; and browsing the web with the new version of Amazon Silk. This book also looks at the relationship of your device to cloud storage; buying and downloading games and apps from the Amazon App Store; buying and reading books; buying and listening to music; transferring your own tunes from your PC; sending documents to your Kindle Fire. Furthermore, this book shows you how to watch videos, use YouTube, and project movies onto your TV from Kindle. Lastly, you learn how to use the built-in camera; share photos with your friends on Facebook; and Skype. Techniques are illustrated step-by-step using photography and screen prints throughout, together with concise, easy to follow text from an established expert in the field, provide a quick guide to the Kindle Fire. Whether you have just bought your first Kindle or a keen user, this brief book will provide you with a firm grasp of the underpinning foundations and equip you with the skills needed to use a Kindle Fire.